Unleashing Potential: Fatima Jinnah Medical University's Global Acclaim and Inspiring Academic Journey (Journal of Fatima Jinnah Medical University, 2023)
Fatima Jinnah Medical University (FJMU), formerly known as Fatima Jinnah Medical College (FJMC), embarked on a transformative journey on July 1st, 2015 when it was awarded the esteemed status of a Medical University by the Government of Punjab from its status as a College for almost 7 decades. This transition from a medical college to a medical university marked a significant milestone in the institute's history.  As FJMU continues to build upon its rich legacy, the transition to a medical university empowers the institution to expand its horizons and delve deeper into the realms of medical knowledge and practice. It provides a fertile ground for fostering innovation, nurturing talent, and producing well-rounded healthcare professionals.          Fatima Jinnah Medical University (FJMU) has, this year, achieved an extraordinary milestone, cementing its position among the top 800 to 1000 universities globally in the esteemed Times Higher Education Impact Ranking. Times Higher Education (THE) is a renowned global university-ranking organization.1 While they do not specifically rank individual words, THE incorporates the Sustainable Development Goals (SDGs) into their ranking methodology. Their evaluations consider universities' contributions towards the SDGs, encouraging institutions to align their research, teaching, and societal impact with these global sustainability targets. This remarkable recognition not only places FJMU among the world's leading academic institutions but also establishes it as amongst the topmost medical university in Punjab, and the third-ranked medical university in Pakistan.2